1989
DOI: 10.1103/physrevlett.62.2801
|View full text |Cite
|
Sign up to set email alerts
|

Limiting fragmentation in oxygen-induced emulsion interactions at 14.6, 60, and 200 GeV/nucleon

Abstract: Pseudorapidity distributions of relativistic singly charged particles in oxygen-induced emulsion interactions at 14.6, 60, and 200 GeV/nucleon are studied. Limiting fragmentation behavior is observed in both the target and projectile fragmentation regions for a central as well as for a minimum-bias sample.Comparisons with the FRITIOF model reveal that the picture of fragmenting strings successfully describes the observed data. PACS numbers: 25.70.NpThe efforts at CERN (60 and 200 GeV/nucleon) and at BNL (14.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(6 citation statements)
references
References 11 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…In spite of this fact limiting fragmentation is found to remain valid over a wide range of energy. This asymptotic property has been observed experimentally in a variety of collision processes such as hadron-hadron, 29,196 hadron-nucleus, 29,197 and nucleus-nucleus 120,124,125,153,[198][199][200][201][202][203][204][205][206] for produced charged hadrons in fragmentation region at different energies. It can be clearly observed that this scaling fea-…”
Section: Limiting Fragmentation or Longitudinal Scaling Observed For mentioning
confidence: 78%
“…In spite of this fact limiting fragmentation is found to remain valid over a wide range of energy. This asymptotic property has been observed experimentally in a variety of collision processes such as hadron-hadron, 29,196 hadron-nucleus, 29,197 and nucleus-nucleus 120,124,125,153,[198][199][200][201][202][203][204][205][206] for produced charged hadrons in fragmentation region at different energies. It can be clearly observed that this scaling fea-…”
Section: Limiting Fragmentation or Longitudinal Scaling Observed For mentioning
confidence: 78%
“…At the stage of nuclear limiting fragmentation [45], nuclear fragments have similar multiplicity and charge distributions. At the stage of hadronic limiting fragmentation, the (pseudo)rapidity spectra of relativistic produced particles in forward (backward) rapidity region have the same or similar shape [46]. For heavy nucleus such as Au and Pb, the initial energy of hadronic limiting fragmentation is possibly about 4 GeV.…”
Section: Resultsmentioning
confidence: 95%
“…Error bar is 1 unit for all data points in case of maximum helium nucleus emission. Data points are from 4 He at 3.7 [11], 12 C at 3.7 [12], 16 O at 2.0 [13], 22 Ne at 3.5 [4], 24 Mg at 3.7 [14], 28 Si at 3.7 [4], 32 S at 2.0 [8], 40 Ar at 1.8 [15], 56 Fe at 1.8 [16], 84 Kr at 1.7 [17], 84 Kr at 0.95 [Present work], 139 La at 0.99 [18] and 197 Au at 0.99 [19].…”
Section: Figure Captionsmentioning
confidence: 99%